Pengaruh Pemberian Minuman Kunyit terhadap Kadar Prostaglandin dan Intensitas Nyeri Haid pada Remaja Putri (Dismenore Primer) - Bq. Yulia Sri Aprian; Suharyo Hadisaputro; Lanny Sunarjo (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Primary dysmenorrhea is a menstrual disorder often experienced by adolescent girls and is characterized by abdominal pain due to increased levels of prostaglandins that trigger uterine contractions. This condition can disrupt daily activities and reduce quality of life. The use of natural ingredients such as turmeric (Curcuma longa) containing curcumin is known to have anti- inflammatory and analgesic effects, and has the potential to reduce prostaglandin levels and the intensity of menstrual pain. This study aims to analyze the effect of providing turmeric drinks on prostaglandin levels and menstrual pain intensity in adolescent girls (primary dysmenorrhea). This research method is a quasi-experimental with a pretest and posttest with a control group design. Through a non-probability sampling technique, 40 respondents were divided into two groups: the intervention group was given a turmeric drink twice a day with a total dose of 30g of turmeric, 2 times a day, 5g dissolved in 200ml of water, given for 3 days, and the control group with warm compresses twice a day for 15 minutes for 3 days. The variables consisted of: the independent variable of turmeric drink, warm compress, the intermediate variable of prostaglandin levels, and the dependent variable of pain  intensity.  Data  analysis  used  the  Levene  Test,  Mann- Whitney, and Wilcoxon. The results of the study Giving turmeric drink 2 times a day with a total dose of 30gr drunk 2 times a day as much as 5gr dissolved in 200ml of water given for 3 days showed an effect seen from the decrease in the number of Numeric Rating Score NRS scores in the turmeric drink intervention group starting from posttest I, Posttest II and Posttest III which were lower with an average value of 0.25. The average score of prostaglandin levels in the intervention group in the pretest was 147.58 decreased to 94.27 in posttest III. Showing that turmeric drink drunk with a total dose of 30gr drunk 2 times a day as much as 5gr dissolved in 200ml of water given for 3 days has an effect on the intensity of menstrual pain in adolescent girls through prostaglandin levels. Keywords: Adolescent Girls, Dysmenorrhea, Prostaglandin Level, Turmeric Drink.